Gut microbiota in irritable bowel syndrome: a narrative review of mechanisms and microbiome-based therapies - Li, Xuemei; Yuan, Qiang; Huang, Hui; Wang, Li (Frontiers in Immunology, 2025)
Irritable bowel syndrome (IBS) is a common disorder of gut–brain interaction, and its pathogenesis remains unclear. Dysbiosis of the gut microbiota is associated with IBS. The gut microbiota may modulate IBS symptoms via the epithelial barrier, mucosal immunity, microbial metabolites (e.g., short-chain fatty acids and bile acids), and gut–brain signaling. Currently, dietary approaches, probiotics, prebiotics, rifaximin, and fecal microbiota transplantation show variable benefit; effects are strain-/context-dependent and evidence certainty varies, with adverse-event reporting inconsistent. This narrative review takes a subtype-aware, mechanism-first perspective to summarize microbiota functions, symptom links, and intervention evidence with safety considerations. This review offers new perspectives and insights for precision treatment and microbiome research in IBS.